2012
DOI: 10.7160/eriesj.2012.050303
|View full text |Cite
|
Sign up to set email alerts
|

Stress Coping Strategies at University Students - Part I: Gender Differences

Abstract: The aim of present study is to investigate the particularities of using various stress coping strategies by undergraduate students at the Czech University of Life Sciences (CULS) with a special regard to the balance between positive and negative stress coping strategies, and resulting consequences. Authors focused on comparing differences in the use of coping strategies between standardized scores of the Czech population and student population, as well as on identifying differences in the use of coping strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…We found that women were likely to experience higher levels of stress, more psychosomatic symptoms, to use more emotion focused coping strategies (i.e., use of emotional support) and to use less the humour as a coping strategy. These findings are in accordance with previous studies that found similar patterns in terms of gender differences (Amaral et al 2018;Brougham et al 2009;Chýlová and Natovová 2012;Kosmala-Anderson and Wallace 2007;Ribeiro et al 2018). It is possible that women are more worried about their academic performance viewing their education as a way to accomplish their life goals; and for that reason, tend to experience more stress and consequently more psychosomatic reactions, in comparison to men (Kosmala-Anderson and Wallace 2007; Ribeiro et al 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that women were likely to experience higher levels of stress, more psychosomatic symptoms, to use more emotion focused coping strategies (i.e., use of emotional support) and to use less the humour as a coping strategy. These findings are in accordance with previous studies that found similar patterns in terms of gender differences (Amaral et al 2018;Brougham et al 2009;Chýlová and Natovová 2012;Kosmala-Anderson and Wallace 2007;Ribeiro et al 2018). It is possible that women are more worried about their academic performance viewing their education as a way to accomplish their life goals; and for that reason, tend to experience more stress and consequently more psychosomatic reactions, in comparison to men (Kosmala-Anderson and Wallace 2007; Ribeiro et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“…1. Based on previous studies we hypothesised that college women will report more perceived stress (e.g., Amaral et al 2018;Brougham et al 2009;Ribeiro et al 2018), more emotion-focused coping strategies such as obtain emotional support or deny guilt (e.g., Amaral et al 2018;Brougham et al 2009;Chýlová and Natovová 2012), more emotion dysregulation (Lafrance Robinson et al 2014; Weinberg and Klonsky 2009), higher negative affect (Amaral et al 2018) and more psychosomatic symptoms (Kosmala-Anderson and Wallace 2007). 2.…”
Section: The Present Studymentioning
confidence: 99%
“…The authors of this paper examined the particularities of various stress coping strategies (measured by standardized stress coping strategies questionnaire SVF 78) used by undergraduate university students. The first part of the results was described in: "Stress coping strategies among university students -part I: Gender differences" (Chýlová and Natovová, 2012). That paper explicitly dealt with a comparative analysis of the role of gender as a variable in relation to stress coping strategies, and the balance between the use of positive and negative strategies.…”
Section: Introductionmentioning
confidence: 99%